2021
DOI: 10.1259/bjr.20210707
|View full text |Cite
|
Sign up to set email alerts
|

Role of contrast-enhanced ultrasound in assessing indeterminate renal lesions and Bosniak ≥2F complex renal cysts found incidentally on CT or MRI

Abstract: Objectives: To investigate the impact of Contrast-enhanced ultrasound (CEUS) in reclassifying incidental renal findings categorized as indeterminate lesions (IL) or Bosniak ≥ 2F complex renal cysts (CRC) on Computed tomography (CT) or Magnetic resonance imaging (MRI). Methods: We retrospectively included forty-four subjects who underwent CEUS between 2016–2019 to assess 48 IL (n = 12) and CRC (n = 36) incidentally found on CT or MRI. CEUS was performed by one radiologist with 10 year of experience with a sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In these cases CEUS can bring supplementary data due to its capacity of the detection of blood flows in small lesions, hypovascular tumors and in thin septa [4,9] being more sensitive than CT [10]. In our patient the CEUS examination demonstrated the presence of vascularization in the arterial phase, followed by a wash-out earlier than the rest of the organ in venous phase, which was the sign of a malignant tumor.…”
Section: Discussionmentioning
confidence: 50%
“…In these cases CEUS can bring supplementary data due to its capacity of the detection of blood flows in small lesions, hypovascular tumors and in thin septa [4,9] being more sensitive than CT [10]. In our patient the CEUS examination demonstrated the presence of vascularization in the arterial phase, followed by a wash-out earlier than the rest of the organ in venous phase, which was the sign of a malignant tumor.…”
Section: Discussionmentioning
confidence: 50%
“…6 It was originally described using computed tomography (CT) imaging but other modalities, such as magnetic resonance imaging (MRI), ultrasound (US), or contrast-enhancement ultrasound (CEUS), are now being used to help better delineate these lesions. [7][8][9][10][11][12][13][14][15][16][17] For patients first identified with a complex cyst (Bosniak classification >2) on US, contrastenhanced, cross-sectional imaging is recommended to better characterize the cyst.…”
Section: █ Recommendationmentioning
confidence: 99%
“…The superior temporal and (in case of optimal patient body habitus) spatial resolution gives this technique distinct advantage in evaluating subtle differences in contrast enhancement, coupled with the fact that the most widely used CEUS contrast agent (SonoVue/Lumason) remains intravascular. It has been demonstrated that CEUS has distinct advantage over CT in the depiction of internal septation, intracystic solid component, and their vascularization, thereby being capable of upgrading or reclassifying renal cystic lesions on the Bosniak scale [11][12][13][14]. It has also been shown recently that CEUS is an excellent choice for follow-up of equivocal (Bosniak 2F) lesions [15].…”
Section: Introductionmentioning
confidence: 99%